Dynamics of Power in Dutch Integration Politics From Accommodation to Confrontation - Uitermark, Justus (Solidarity and Identity, 2012)
Integration politics in the Netherlands has changed dramatically between 1990 and 2005. Whereas ethnic and religious differences were hitherto pacified through accommodation, a new and increasingly powerful current in Dutch politicsproblematizes the presence of minorities.This development represents a challenge to sociologists and political scientists: how to map and explain drastic changes?Arguing that extant approaches are better at explaining continuity than change, this book develops a distinct approach to the study of dynamic power relations to understand drastic transformations in the national debate as well as urban governance.